Design and Evaluation of a Versatile and Efficient Receiver-Initiated Link Layer for Low-Power Wireless - Dutta, Prabal; Dawson-Haggerty, Stephen; Chen, Yin; Liang, Chieh-Jan Mike; Terzis, Andreas (SenSys (ACM Conference on Embedded Network Sensor Systems), 2010)
We present A-MAC, a receiver-initiated link layer for low-power wireless networks that supports several services under a unified architecture, and does so more efficiently and scalably than prior approaches. A-MAC’s versatility stems from layering unicast, broadcast, wakeup, pollcast, and discovery above a single, flexible synchronization primitive. A-MAC’s efficiency stems from optimizing this primitive and with it the most consequential decision that a low-power link makes: whether to stay awake or go to sleep after probing the channel. Today’s receiver-initiated protocols require more time and energy to make this decision, and they exhibit worse judgment as well, leading to many false positives and negatives, and lower packet delivery ratios. A-MAC begins to make this decision quickly, and decides more conclusively and correctly in both the negative and affirmative. A-MAC’s scalability comes from reserving one channel for the initial handshake and different channels for data transfer. Our results show that: (i) a unified implementation is possible; (ii) A-MAC’s idle listening power increases by just 1.12× under interference, compared to 17.3× for LPL and 54.7× for RI-MAC; (iii) A-MAC offers high single-hop delivery ratios, even with multiple contending senders; (iv) network wakeup is faster and far more channel efficient than LPL; and (v) collection routing performance exceeds the state-of-the-art.